Pengaruh Karya Bubur Kertas Terhadap Sikap Peduli Lingkungan Pada Pembelajaran Seni Rupa Kelas IV SD - Rachmadini, Mutiara; Yusnia (JURIDIKDAS (Jurnal Riset Pendidikan Dasar), 2025)
This research aims to know the effect of artwork paper mache on environmental awareness in the art education of fourth-grade students in The Elementary School of Bengkulu City. This type of research is quantitative with methods Pre-Eksperimental Design with research design One Group Pretest-Posttest Design. The population in this research consisted of Elementary Schools in Cluster V of Bengkulu City. The sample for that research was Class IVB from State Elementary School 02 Bengkulu City. The research results show the questionnaire with Likert scale measurements. The results of this assessment indicate a significant difference between the pretest and post-test data. This is evidenced by the t-value of 4.746 and the Sig. (2-tailed) value of 0.001, with a significance level of 2.073, as the t-value is less than the t-table value (4.746 > 2.073). Additionally, the Sig. (2-tailed) value of 0.001 < 0.025, confirming the acceptance of the alternative hypothesis (Ha). It can be concluded that there is a significant difference in environmental awareness between the pre-test and post-test data. Thus, the results indicate an effect of artwork paper mache on environmental awareness in the art education of fourth-grade students in the Elementary School of Bengkulu City.